Peran Koperasi dalam Meningkatkan Kesejahteraan Masyarakat - Ach Zakaria; Erik Kantona (Jurnal Manajemen Bisnis Digital Terkini, 2025)
Cooperatives have a strategic role in improving people's welfare, especially in developing countries like Indonesia. As one of the pillars of the national economy, cooperatives function as a forum for community cooperation in meeting economic needs in a fair and sustainable manner. This study aims to analyze the role of cooperatives in improving people's welfare through a library research approach. The method used in this study is a descriptive method with deductive data analysis techniques, where data is obtained from various sources such as books, journals, and laws and regulations related to cooperatives. The results of the study show that cooperatives contribute to community economic empowerment by providing more inclusive access to capital, creating jobs, and improving social welfare through education and health programs. With the principle of mutual cooperation and democratic management, cooperatives can be a solution in creating a more independent and prosperous people's economy. Therefore, consistent regulatory support and increased human resource capacity are needed so that cooperatives can function optimally in community economic development.